Sufism Values in Fast Prayer Sambayang Marapas Study in West Sulawesi - Nurfadil (Mauriduna: Journal of Islamic Studies, 2024)
This research uncovers the impropriety of fast prayer Sambayang Marapas and reveals the Sufism values of the practitioners of Sambayang Marapas or fast parayer in Sulawesi. Based on the situation in the field, the worship has triggered the emergence of pro and contra debates. Because many parties have begun to view the practice of Samabayang Marapas as a deviation and classified as a cult and far from the values and practices of diversity in Islam, while for some people including worshipers see that Sambayang Marapas is a not deviant teaching because the originator of the fast prayer is a person known as an awali Allah, and the worshipers also hold that the only one has the right to judge the validity or invalidity of prayer is Allah SWT.